Purifikasi Islam dalam Gerakan Padri di Minangkabau - Haedar Nashir (Unisia, 2008)
The Padri Movement, also known as the White Group Movement, grown up in Minangkabauin 1821 – 1837, on one side, had been a strong and militant struggle against Dutch colonizationin Sumatra. On the other side, this movement also raised as a power of reform,bringing together a strong and militant mission of Islamic Purification. This movement hadraised a violence controversy, both when it conflicted with traditional power and when itexpanded its areas of movement to the Batak Land. In the perspective of Sociology, boththe Padri Movement and its militant and violence actions brought in every expanded socialor religious movement cannot be separated one and each other. This is caused by the factthat such a movement is closely related to a strict religious ideology and faith, and at onceit also closely related to a complicated sociological condition at that time. Therefore, amulti-perspective is necessary to understand complicated socio-religious movements.Keywords: Padri Movement, Religious Movement, Islamic Purification.